Chirurgische Möglichkeiten der Glaukomtherapie - Dietlein, Thomas S.; Rosentreter, André (Augenheilkunde up2date, 2018)
Die Glaukomchirurgie erfährt einen Innovationsschub insbesondere durch neue Mikroimplantate. Auch lange bestehende glaukomchirurgische Verfahren, wie die Trabekulektomie oder die Drainageimplantatchirurgie, erleben eine Aufwertung durch eine Verbesserung ihres Risiko-Nutzen-Profils. Dieser Beitrag gibt einen Überblick über die aktuellen chirurgischen Optionen der Glaukombehandlung.During the last few years, there has been a considerable capacity of innovations in glaucoma surgery owing to new micro-stents increasing the aqueous outflow via transscleral routes, via the trabecular meshwork or the suprachoroidal space. These interventions can be easily performed in combination with small-incision cataract surgery. Even the well-known filtering procedures, trabeculectomy and drainage device surgery, formerly perceived as being outdated, re-achieve better reputation owing to refinements in surgical technique and improved surgical experience. Although enthusiasm is understandable, considering the technical advances, we must wait for clinical long-term results and compare the new procedures with the established ones.
Keywords: Augendruck; Glaukomchirurgie; Glaukomimplantat; Trabekulektomie